USING OF TESTING IN ENGLISH LANGUAGE LESSONS - Niyozova Yulduz Tashmuratovna (Bright Mind Publishing, 2025)
The article deals with the use of tests in the process of teaching a foreign language in universities. The purpose of the article is to identify the more effective sides of testing. Tests can contribute to further self-education and improvement of students' knowledge at all levels of education.
Keywords: Testing, efficient way, foreign language, knowledge, hemis, educational system, assessment.